Community-acquired Pneumonia: A Global Perspective - Waterer, Grant W. (Seminars in Respiratory and Critical Care Medicine, 2016)
Community-acquired pneumonia (CAP) is a global disease responsible for a large proportion of deaths and having significant economic cost. As diagnostic tools have increased in sensitivity, our understanding of the etiology of CAP has begun to change with a significant increase in confirmed viral infections and the recognition that multiple pathogens are frequently present. Empiric therapy remains the standard of care and guidelines are mostly based on published data from the United States or Europe. Blindly applying guidelines without any consideration of local etiological differences can lead to a risk of under or overtreatment. Several pathogens are particularly problematic in the setting of CAP in some regions as they are not covered by standard guidelines; in particular, Mycobacterium tuberculosis, Burkholderia pseudomallei, and Acinetobacter baumanii. Overtreatment of patients meeting guideline criteria for healthcare-associated pneumonia is also a problem as this categorization probably only applies to a limited number of areas in the United States. New pathogens are emerging more frequently, as evidenced by severe acute respiratory syndrome, Middle East respiratory syndrome, influenza A H1N1 09, and avian influenza, all of which have global ramifications and good clinicians need to stay informed of evolving threats. There are clearly differences in outcomes from CAP across the globe, but accurately comparing them is difficult given the vast differences in age, comorbidities, and access to healthcare. Improved quality of outcome databases will be a key driver of quality improvement in coming years.
Keywords: community-acquired pneumonia; etiology; empiric therapy; guidelines